VIDEO DOCUMENTARY WEAVING CRAFTS IN JAJAR VILLAGE, TRENGGALEK REGENCY AS INFORMATION MEDIA - Panca, Mochamad Ridho; Eizzi Irsyada, Abdulloh (Jurnal Desain Komunikasi Visual Asia, 2021)
Crafts are goods that are produced through hand skills. Crafts produce works that attach importance to the value of beauty as decoration or use, one of which is ikat weaving. Ikat weaving is a craft produced from strands of weft or warp threads that are first tied, then dyed, and then woven. One of them is the Telagasari Weaving craft in Trenggalek Regency. Because Telagasari Weaving is the only ikat weaving craft in Trenggalek. Telagasari weaving has contributed a lot to the introduction and development of weaving in Trenggalek. The development of ikat in Trenggalek is quite slow due to the geographical location of Trenggalek in the form of highlands and mountains. Another factor is the lack of media information about the Trenggalek traditional weaving craft industry. Therefore, it is necessary to make some kind of documentation for information media in the form of audio-visual, so that people know that Trenggalek has a weaving industry.